2023
DOI: 10.1093/jleuko/qiad010
|View full text |Cite
|
Sign up to set email alerts
|

Water channel aquaporin 4 is required for T cell receptor mediated lymphocyte activation

Abstract: Aquaporins are a family of ubiquitously expressed transmembrane water channels implicated in a broad range of physiological functions. We have previously reported that Aquaporin 4 (AQP4) is expressed on T cells and that treatment with a small molecule AQP4 inhibitor significantly delays T cell mediated heart allograft rejection. Using either genetic deletion or small molecule inhibitor, we show that AQP4 supports T cell receptor mediated activation of both mouse and human T cells. Intact AQP4 is required for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In previous work, we did not detect AQP4 protein or mRNA in WT murine peripheral T cells ( 51 ). However, one group reported that T cell AQP4 deficiency reduced TCR-mediated signaling, although they did not detect any change in thymocyte subsets ( 52 ). It should be recognized that it was the AQP4-specific T cells from AQP4 −/− but not WT mice that induced CNS autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, we did not detect AQP4 protein or mRNA in WT murine peripheral T cells ( 51 ). However, one group reported that T cell AQP4 deficiency reduced TCR-mediated signaling, although they did not detect any change in thymocyte subsets ( 52 ). It should be recognized that it was the AQP4-specific T cells from AQP4 −/− but not WT mice that induced CNS autoimmune disease.…”
Section: Discussionmentioning
confidence: 99%